1992
DOI: 10.1083/jcb.117.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of kinesin expression in cultured hippocampal neurons using antisense oligonucleotides.

Abstract: . Kinesin, a microtubule-based forcegenerating molecule, is thought to translocate organelles along microtubules. To examine the function of kinesin in neurons, we sought to suppress kinesin heavy chain (KHC) expression in cultured hippocampal neurons using antisense oligonucleotides and study the phenotype of these KHC "null" cells. Two different antisense oligonucleotides complementary to the KHC sequence reduced the protein levels of the heavy chain by greater than 95% within 24 h after application and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
124
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 56 publications
(60 reference statements)
15
124
1
Order By: Relevance
“…Five to 6 h later transfection oligos were added at a concentration of 0.5 M. Twelve hours later oligos were added at a concentration of 0.25 M. Video microscopy was performed 26 -28 h after transfection. Treating cells with oligos at 50 M (Ferreira et al, 1992) led to similar results, except that even more structures changed direction of movement (our unpublished results).…”
Section: Antisense Treatmentsupporting
confidence: 65%
See 2 more Smart Citations
“…Five to 6 h later transfection oligos were added at a concentration of 0.5 M. Twelve hours later oligos were added at a concentration of 0.25 M. Video microscopy was performed 26 -28 h after transfection. Treating cells with oligos at 50 M (Ferreira et al, 1992) led to similar results, except that even more structures changed direction of movement (our unpublished results).…”
Section: Antisense Treatmentsupporting
confidence: 65%
“…Oligonucleotides used were GCCGGGTCCGC-CATCTTTCTGGCAG, the inverse complement of the rat nucleotides Ϫ11 to ϩ 14 of conventional kinesin heavy chain (KHC), and CTGCCAGAAAGATGGCGGACCCGGC, the corresponding sense oligonucleotide (Ferreira et al, 1992). Five to 6 h later transfection oligos were added at a concentration of 0.5 M. Twelve hours later oligos were added at a concentration of 0.25 M. Video microscopy was performed 26 -28 h after transfection.…”
Section: Antisense Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we should stress that it does not necessarily mean that microtubule motors are not involved in neurite elongation in PC12 cells. For example, Ferreira et al (1992) showed that antisense nucleotides to kinesin heavy chain inhibited neurite elongation in cultures of rat hippocampal neurons. If this is the case for PC12 cells as well, it is possible that some other member of kinesin superfamily rather than kinesin per se is involved in generation of neuronal polarity and this member probably is not inhibited by our antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, antisense oligonucleotide inhibition of KHC in cultured rat astrocytes (Feiguin et al, 1994) and gene disruption in cultured mouse extraembryonic cells (Tanaka et al, 1998) did not prevent brefeldin A-induced Golgi-to-ER membrane transfer. With regard to Golgi-to-plasma membrane vesicle transport, antisense oligonucleotide inhibition of KHC in cultured vertebrate neurons impaired delivery of vesicles containing certain synaptic proteins to axon terminals (Ferreira et al, 1992). In contrast, Khc mutations in Drosophila and Caenorhabditis elegans did not prevent the accumulation of normal levels of synaptic vesicles at axon terminals (Hall et al, 1991;Gho et al, 1992).…”
Section: Discussionmentioning
confidence: 99%